Effects of ultrasonic modification on physicochemical and structural properties of pomelo peel soluble dietary fiber extracted by alkali - Yang Ye; Fei Chen; Zhaoyi Lu; Jingyu Xiang; Guixiang Jia; Mingyi Xu; Yang Liu; Yang Wang; Xiaoling Wang (Scientific Reports)
Abstract Pomelo peel, as a by-product of pomelo, is abundant with in soluble dietary fiber (SDF). The SDF obtained from pomelo peel using an alkaline solution was labeled ASDF, and the ASDF that was modified using ultrasound was labeled UASDF. An investigation was conducted into the physicochemical, structural, and functional properties of the samples were investigated. The investigative results show that ultrasound modification increases SDF content from 24.0 to 28.9%, with an improvement in the water-holding and swelling capacity of SDF. However, there is little effect on the oil-holding capacity. As revealed by the structural characterization both ASDF and UASDF exhibit the typical characteristics of cellulosic polysaccharides, but UASDF is 5.63% less crystalline than ASDF, resulting in a looser porous structure. In addition, UASDF possesses high glucose adsorption capacity (29.98 mg/g) and high cholesterol adsorption capacity in the small intestine (pH = 2, 20.86 mg/g; pH = 7, 25.11 mg/g). UASDF also exerts a more significant antioxidant effect, particularly ABTS free radical scavenging rate of 80.97% (5 mg/mL). The superior adsorption capacity and antioxidant ability of UASDF are attributed to its structure. These results demonstrate that pomelo peel is applicable as an inexpensive natural dietary fiber, and that UASDF possesses excellent functional characteristics.